Control and monitoring of an intra-aortic balloon pump for cardiac assist - Holmes à Court, Robert Leonard (Department of Electrical Engineering, 2016)
An anatomical and physiological background to the heart as a pump, followed by a description of the causes and results of cardiogenic shock is given. A survey of the achievements of other researchers in this field is included. The design of a system for controlling and monitoring the Intra-Aortic Balloon Pump is described. A narrow band-pass filter is used to reduce noise and limit the input to the detector to the spectrum within which the R-wave of an ECG signal lies. A safety circuit to prevent the heart pumping against an inflated balloon is incorporated. History of the 8 secs preceding any instant is available. A description of the medical tests carried out so far is given.